PIMPIN organised a workshop on Al-Quran reading using sign language and braille - Nur Sa’adatul Afzan, Jusoh (2019)
Concerned over the plight of people with disabilities (OKU), Universiti Malaysia Pahang (UMP)’s Islamic Centre and Human Development (PIMPIN) organised a special workshop for the public including for the disabled especially those with hearing and sight impairment on March 26, 2019.